News Media Framing of Self-Harm in Australia - Staniland, Lexy; Hasking, Penelope; Lewis, Stephen P.; Boyes, Mark (2022)
As a conduit of knowledge for the general public, news media inform the development and maintenance of attitudes and beliefs about a range of topics, including mental health and related behaviors. News media portrayals of such topics can, therefore, contribute to stigma—the culmination of harmful stereotypes, prejudice, and discrimination. A topic of increasing media and research interest is self-harm, a behavior that is still poorly understood and highly stigmatized. Despite the potential for news media to be a source of self-harm stigma, few investigations of such portrayals have been conducted. To understand how news media portrays self-harm, a qualitative media framing analysis was conducted on 545 news articles published in Australia during 2019. Six frames were identified: Inevitably Suicidal, A Tragic Outcome, Mentally Unwell, An Epidemic, Threatening and Dangerous, and A Manipulative Tactic, each drawing on a broader narrative of pathology, instability, and damage. Use of problematic language and a lack of definitional clarity reinforced these frames. While the analyzed articles are limited to an Australian context, findings demonstrate continued misrepresentations of self-harm, which arguably contribute to ongoing self-harm stigma. Greater education and support for journalists reporting about self-harm is needed.